2021
DOI: 10.4143/crt.2020.1270
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Symptom-Focused Quality of Life Questionnaire (KOQUSS-40) for Gastric Cancer Patients after Gastrectomy

Abstract: Purpose Patients who have undergone gastrectomy have unique symptoms that are not appropriately assessed using currently available tools. This study developed and validated a symptom-focused quality of life (QoL) questionnaire for patients who have received gastrectomy for gastric cancer. Materials and Methods Based on a literature review, patient interviews, and expert consultation by the KOrean QUality of life in Stomach cancer patients Study group (KOQUSS), the initial item pool was developed. Two large-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Studies also reported on coping strategies, adjustment and acceptance of GC, nutritional status, unmet needs, and educational and self-care interventions. Six papers [23,[41][42][43][44][45], including 5 from non-East Asian countries, reported qualitative studies; three involved interviews with patients about symptoms experienced, such as gastrointestinal problems, fatigue, weight loss, and dietary restrictions, [41][42][43] and one about treatment preferences [44] whereby maintenance of selfcare and minimising toxicities were rated as priorities. Two incorporated qualitative methodologies as part of a questionnaire development process [23,45].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also reported on coping strategies, adjustment and acceptance of GC, nutritional status, unmet needs, and educational and self-care interventions. Six papers [23,[41][42][43][44][45], including 5 from non-East Asian countries, reported qualitative studies; three involved interviews with patients about symptoms experienced, such as gastrointestinal problems, fatigue, weight loss, and dietary restrictions, [41][42][43] and one about treatment preferences [44] whereby maintenance of selfcare and minimising toxicities were rated as priorities. Two incorporated qualitative methodologies as part of a questionnaire development process [23,45].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to bespoke questions added to match the researchers' areas of interest, eight measures [27,28,45,[54][55][56][57][58], were developed in East Asia, and the PGAS45 [27] includes clinically important items selected by the Japan Post-gastrectomy Syndrome Working Party. Across all measures, the most widely assessed construct pertains to physical symptoms and this is particularly true for the GC or gastrointestinal specific measures which focus on gastrointestinal symptoms of disease and treatment such as gastrectomy.…”
Section: Measures Used To Capture the Hrqol Issues Of Patients With Gcmentioning
confidence: 99%
“…In this study, KOQUSS-40 will be used to assess the QoL. 5 Frequent follow-up indicates frequent counselling, education and prescription, and these delicate management strategies help patients in self-controlling their symptoms, resulting in better physical, social and emotional functions. KOQUSS-40 focuses on postgastrectomy symptoms and we will evaluate whether there is a significant difference in KOQUSS-40 questionnaire scores in individuals with different follow-up intervals.…”
Section: Discussionmentioning
confidence: 99%
“…QoL will be assessed using three types of questionnaires; the KOrean QUality of life in Stomach cancer patients Study group-40 (KOQUSS-40), the European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire (QLQ) Core 30 (C30), and the stomach cancer-specific module (EORTC QLQ STO22). [5][6][7] KOQUSS-40 is a symptom-focused questionnaire for patients undergoing gastrectomy for Open access gastric cancer. It consists of 40 items in 11 domains and its scoring ranges from 0 (the worst) to 100 (the best) for each domain.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…At present, radical gastrectomy is the first-line treatment for GC that can prolong patients’ survival time ( 3 , 4 ). As surgery for GC gradually shifts toward minimally invasive approaches that can minimize trauma and postoperative complications and accelerate recovery ( 5 , 6 ), postoperative gastrointestinal symptoms (PGISs) such as abdominal distention, pain, and vomiting continue to exist that affect quality of life ( 7 ).…”
Section: Introductionmentioning
confidence: 99%